2010
DOI: 10.1021/es101039d
|View full text |Cite
|
Sign up to set email alerts
|

Marine Natural Products, the Halogenated 1′-Methyl-1,2′-bipyrroles, Biomagnify in a Northwestern Atlantic Food Web

Abstract: Halogenated 1'-methyl-1,2'-bipyrroles (MBPs) are putative marine natural products that accumulate in marine mammal blubber in similar concentrations and patterns to biomagnifying organic pollutants. Here we measure concentrations of MBPs and 2,2',4,4',5,5'-hexachlorobiphenyl (CB-153) in 40 samples composed of eight fish species, two squid species, and six species of marine mammals. To determine their trophic positions and to further investigate influence of prey preference, we also measured the stable carbon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
2
20
1
Order By: Relevance
“…Pangallo et al 51 suggested that MBPs may have an ocean-basin specific distribution, as evidenced by the dominance of brominated MBPs in the North Atlantic and highly-chlorinated derivatives in the South Pacific. The addition of our results, however, suggests a difference between the northern and southern hemisphere 52 , where SE Pacific and SW Atlantic odontocetes exhibit a dominance of chlorinated MBPs 48,49 and NE Pacific and NW Atlantic odontocetes exhibit a dominance of brominated MBPs 12,17,51,53 .…”
Section: Resultscontrasting
confidence: 63%
“…Pangallo et al 51 suggested that MBPs may have an ocean-basin specific distribution, as evidenced by the dominance of brominated MBPs in the North Atlantic and highly-chlorinated derivatives in the South Pacific. The addition of our results, however, suggests a difference between the northern and southern hemisphere 52 , where SE Pacific and SW Atlantic odontocetes exhibit a dominance of chlorinated MBPs 48,49 and NE Pacific and NW Atlantic odontocetes exhibit a dominance of brominated MBPs 12,17,51,53 .…”
Section: Resultscontrasting
confidence: 63%
“…HNP profiles have been shown to be unique to different marine species and ecotypes within a geographic region (Dorneles et al, 2010;Hauler et al, 2013;Pangallo and Reddy, 2010;Shaul et al, 2015). The species in this study displayed nearly unique HNP profiles ( Figure 3).…”
Section: Halogenated Natural Productsmentioning
confidence: 71%
“…The 30 identified halogenated natural products (HNPs) belonged to six different structural classes and accounted for 15% of the HOCs. These compounds are produced by algae or sponges and have a biomagnification potential similar to anthropogenic HOCs (Pangallo and Reddy, 2010). Despite their global distribution and profusion in marine food webs and biota, the health implications of exposure to HNPs are largely unknown (Shaul et al, 2015).…”
Section: Halogenated Natural Productsmentioning
confidence: 99%
“… 31 The modes by which DMBPs and MBPs enter the marine food web have not yet been identified, but MBPs have been shown to biomagnify with increasing trophic level. 62 There is evidence for biosynthesis of DMBPs by marine bacteria, 3 but further research is required to identify the sources and distribution in the Southern California Bight.…”
Section: Discussionmentioning
confidence: 99%